British Political Facts Since 1979 - Butler, D. author. aut Link
XV, 316 p. 1 illus.
Keywords: British Political Facts Since 1979 is the definitive record of the who, the what and the when of British political history from the election of Mrs Thatcher as Prime Minister to the present day. It is a comprehensive reference work that will be invaluable to students of Contemporary British Politics.